Transplantation of Adipose-derived Cells for Periodontal Regeneration: A Systematic Review - Dziedzic, Dilcele S. M.; Mogharbel, Bassam F.; Ferreira, Priscila Elias; Irioda, Ana Carolina; de Carvalho, Katherine Athayde Teixeira (Current Stem Cell Research & Therapy, 2019)
This systematic review evaluated the transplantation of cells derived from adipose tissue for applications in dentistry. SCOPUS, PUBMED and LILACS databases were searched for in vitro studies and pre-clinical animal model studies using the keywords “ADIPOSE”, “CELLS”, and “PERIODONTAL”, with the Boolean operator “AND”. A total of 160 titles and abstracts were identified, and 29 publications met the inclusion criteria, 14 in vitro and 15 in vivo studies. In vitro studies demonstrated that adipose- derived cells stimulate neovascularization, have osteogenic and odontogenic potential; besides adhesion, proliferation and differentiation on probable cell carriers. Preclinical studies described improvement of bone and periodontal healing with the association of adipose-derived cells and the carrier materials tested: Platelet Rich Plasma, Fibrin, Collagen and Synthetic polymer. There is evidence from the current in vitro and in vivo data indicating that adipose-derived cells may contribute to bone and periodontal regeneration. The small quantity of studies and the large variation on study designs, from animal models, cell sources and defect morphology, did not favor a meta-analysis. Additional studies need to be conducted to investigate the regeneration variability and the mechanisms of cell participation in the processes. An overview of animal models, cell sources, and scaffolds, as well as new perspectives are provided for future bone and periodontal regeneration study designs.
Keywords: bone regeneration